Effects of anaerobic training on neuromuscular junction morphology in rat diaphragm muscle - Aguiar, A. F.; Camaçarí De Carvalho, S. [UNESP]; Dal-Pai-Silva, M. [UNESP]; Michelin Matheus, S. M. [UNESP] (My University, 2015)
Aim. The purpose of this study was to test the hypothesis that anaerobic training would promote an increase in the neuromuscular junction (NMJ) diameter of diaphragm muscle in rats. Methods. Male Wistar rats were randomly assigned to either a trained (TR, N.=8) or a control (CO, N.=8) group. The trained group underwent a 5-wk anaerobic training program (5 d·wk-1; 25 sessions) using a water-jump exercise model. The CO group was not exposed to any training stimuli throughout the study. After the 5-wk experiment period, animals were euthanized and the diaphragm muscle was collected to morphometrical (diameter measurement) and ultrastructural (structural features) analysis of the NMJ Results. Anaerobic training promoted a greater increase in the NMJ diameter (+10.8%; P < 0.001) and endurance muscle (+19%; P < 0.001) of the TR group compared with the CO group. No changes (P > 0.05) in the NMJ structural features (pre- and post-synaptic components) were observed between the groups. Moreover, there was a significant positive correlation between the NMJ diameter and the muscular endurance (r = 0.72; P = 0.0001). Conclusion. Our results indicate that anaerobic training results in significant increase in diaphragm NMJ diameter, and that these morphological adaptations are well correlated with endurance exercise performance. This suggests that diaphragm muscle NMJ remodeling may play a role in fatigue.
Keywords: Exercise; Fatigue; Motor endplate; Physical endurance; Synapses